IMPLEMENTATION MODEL OF MULTILEVEL FOREIGN LANGUAGE TRAINING - Larisa E. Babushkina; Svetlana I. Piskunova (Высшее образование в России)
In the framework of the discourse, the article presents implementation model of multilevel foreign language training in pedagogical institution. The main objective of the proposed model is to create pedagogical conditions for the improvement of student's personality, which is consciously and with motivation capable to acquire linguistic, communicative and sociocultural competences for realization of foreign language, cultural and professional communication. It justifies the conclusion about the effectiveness of revealed pedagogical conditions, which are aimed at increasing the level offoreign language proficiency. Possible ways and means of training and organizational forms of the educational process are discussed. It is noted that in the framework of designed model the result of the implementation of multilevel foreign language training in pedagogical institution is the rise of the level of foreign language proficiency.